Comparing serum protein levels can aid in differentiating HPV-negative and -positive oropharyngeal squamous cell carcinoma patients - Dickinson, Amy (PLoS One, 2020)
BACKGROUND: The surrogate immunohistochemical marker, p16(INK4a), is used in clinical practice to determine the high-risk human papillomavirus (HPV) status of oropharyngeal squamous cell carcinomas (OPSCC). With a specificity of 83%, this will misclassify some patients compared with direct HPV testing. Patients who are p16(INK4a)-positive but HPV DNA-negative, or RNA-negative, may be unsuitable for treatment de-escalation aimed at reducing treatment-related side effects. We aimed to identify cost-effective serum markers to improve decision making for patients at risk of misclassification by p16(INK4a) alone. METHODS: Serum proteins from pre-treatment samples of 36 patients with OPSCC were identified and quantified using label-free mass spectrometry-based proteomics. HPV-status was determined using p16(INK4a)/HPV DNA and E6/E7 mRNA. Serum protein expressions were compared between groups of patients according to HPV status, using the unpaired t-test with a Benjamini-Hochberg correction. ROC curves (AUC) were calculated with SPSS (v25). RESULTS: Of 174 serum proteins identified, complement component C7 (C7), apolipoprotein F (ApoF) and galectin-3-Binding Protein (LGALS3BP) significantly differed between HPV-positive and -negative tumors (AUC ranging from 0.84–0.87). ApoF levels were more than twice as high in the E6/E7 mRNA HPV-positive group than HPV-negative. CONCLUSIONS: Serum C7, ApoF and LGALS3BP levels discriminate between HPV-positive and HPV-negative OPSCC. Further studies are needed to validate these host immunity-related proteins as markers for HPV-associated OPSCC.